Sint Maarten Public Expenditure Review - World Bank (World Bank, Washington, DC, 2020)
Sint Maarten is a high-income small island state located in the Caribbean that occupies the southern half of the island shared with the French overseas collectivity of Saint Martin. Sint Maarten is one of the six islands in the Caribbean that form part of the Kingdom of the Netherlands and since the dissolution of the former Netherlands Antilles on October 10, 2010 it has an autonomous constitutional status as a separate country within the Kingdom. As a small island state, Sint Maarten has an open and largely tourism-based economy. The island belongs to the Leeward Islands, a group of islands located where the northeastern Caribbean Sea meets the western Atlantic Ocean within the Caribbean hurricane belt. Sint Maarten has been exposed to numerous hurricanes, including Luis in 1995, Lenny in 1999, and Irma and Maria in 2017. The PER consists of four interconnected chapters: (i) macro-fiscal developments, (ii) health, (iii) social protection, and (iv) education. The main findings of these detailed chapters are brought together and summarized in this synthesis report. The focus of the PER on challenges in revenue generation and tax administration, public financial management, health and long-term care, social protection and pension systems, and education is motivated by the potential impact of policy and institutional reform in each of these areas on public finance.